Key stakeholders’ experiences, knowledge and perspectives regarding care quality for breast cancer in South-West Nigeria - Alabi, Adewumi; Ainsworth, Victoria; Lawal, Abdulrazzaq; Kizub, Darya; Chin, Jennifer; Woodmark, Carly; Omidiji, Olubukola; Adegboyega, Bolanle; Sowunmi, Anthonia; Ogunyemi, Adedoyin; Swanson, William; Joseph, Adedayo; et al. (Frontiers in Oncology, 2025)
The landscape of breast cancer care in Nigeria is complex, with various structural and individual barriers impacting patient care. Breast cancer (BC) is the most common cancer and a leading cause of cancer deaths among women worldwide. In Africa, the cancer burden is expected to rise significantly, with projections estimating an increase of 50% by 2050. Rising incidence rates and barriers to care contribute to a healthcare crisis, leading to late-stage presentation and high mortality rates for women with breast cancer in Nigeria. Quality healthcare must be patient-centered, involving stakeholders - patients, clinical and community partners, and other healthcare stakeholders to achieve a desired outcome. Understanding the cancer journey from different perspectives allows for targeted approaches for increasing access to quality healthcare as well as reducing morbidity and mortality rates. To address this, healthcare provider perspectives about breast cancer care were compared with the lived experiences of breast cancer patients to emphasize the need to increase access and quality of care. A mixed method study was conducted in 2 phases: Phase I: 3 Focus group discussions (FGDs) with breast cancer patients and their care givers were conducted at the NSIA-LUTH Cancer Centre in Lagos, Nigeria. Phase II: A pre and post-survey of a continuing medical education course focused on breast cancer was delivered to healthcare providers in southwest Nigeria. Survey responses regarding causes for delays and barriers to care indicated financial strain, fear, and alternative treatments as the largest hurdles, coinciding with patient testimony from the FGD. Fear of mastectomy was a perceived barrier to care for 90% of healthcare providers while 87% and 86% of providers perceived seeking spiritual and herbal treatments as the largest delays of care. Despite this, a significant number of focus group participants (39%) presented within the first month of noticing a breast symptom to a proper healthcare provider. Data from our study reports that 70% of patients receive help from family to fund treatment highlighting why cancer can be a poverty trap for families and the need for universal health insurance. Half of the focus group participants had a positive interaction with their doctors, with the rest reporting neutral (19%) or even negative (31%) interactions. Our study also reports 42% of healthcare providers feeling only “somewhat” qualified to deal with breast cancer, highlighting the significant need for more education, with a further 14% feeling neutral or negative about their qualification, a potential contributing factor in negative interactions recalled by patients. Knowledge increase was consistent for best practice diagnostic modalities among healthcare providers (p < 0.05). At the same time, items related to symptoms and risks of breast cancer had inconsistent knowledge increases, indicating why further courses like these should be pursued. With the success of the course and the inspiration of breast cancer survivors, a proposed expansion into community awareness is discussed along with enlisting local practitioners in the fight against breast cancer in hopes of lowering the barriers to and delays of care in Nigeria.